2013
DOI: 10.1002/app.40082
|View full text |Cite
|
Sign up to set email alerts
|

Flow improvement of Liaohe extraheavy oil with comb‐type copolymers

Abstract: Liaohe extraheavy oil is a kind of special crude oil with high paraffin and asphaltene contents and a pour point of up to 60 C. To improve its flowability, comb-type poly(maleic alkylamide-co-a-octadecene) copolymers (MACs) with various amidation ratios were synthesized and used. Model oils containing paraffin mixtures with the same average carbon number to Liaohe extraheavy oil with and without asphaltene were prepared to explore the effect of the MACs on paraffin crystallization and asphaltene dispersion, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…DSC curves of MO and CO in the presence and absence of copolymers during cooling are shown in Figure . All of the cooling curves of CO exhibit two distinct peaks, which is probably due to the existence of two groups of crystallizable paraffins whose carbon numbers are significantly different . It is found that the addition of copolymers shifts the onset of paraffin crystallization to a lower temperature and reduces the enthalpy (area of exothermic peaks) of the transition upon cooling for both MO and CO.…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…DSC curves of MO and CO in the presence and absence of copolymers during cooling are shown in Figure . All of the cooling curves of CO exhibit two distinct peaks, which is probably due to the existence of two groups of crystallizable paraffins whose carbon numbers are significantly different . It is found that the addition of copolymers shifts the onset of paraffin crystallization to a lower temperature and reduces the enthalpy (area of exothermic peaks) of the transition upon cooling for both MO and CO.…”
Section: Resultsmentioning
confidence: 92%
“…All of the cooling curves of CO exhibit two distinct peaks, which is probably due to the existence of two groups of crystallizable paraffins whose carbon numbers are significantly different. 35 It is found that the addition of copolymers shifts the onset of paraffin crystallization to a lower temperature and reduces the enthalpy (area of exothermic peaks) of the transition upon cooling for both MO and CO. These effects follow a ranking of MACB > MACP > MACO, coinciding with the rheological and PLM observations.…”
Section: Energy and Fuelsmentioning
confidence: 98%
See 2 more Smart Citations
“…Nowadays, blending crude oil with low concentration of polymer additives appears to be a more effective way of solving those problems caused by wax precipitation. Several kinds of comb‐type polymer additives such as poly(ethylene‐butene) (PEB) and poly(maleic anhydride ‐co‐α‐ olefin) derivatives (MAC) have been reported as cold flow improvers for waxy oil.…”
Section: Introductionmentioning
confidence: 99%